Characteristics of a tattooed population and a possible role of tattoos as a risk factor for chronic diseases: Results from the LIFE-Adult-Study - Theune, Loryn E.; Ghoreishi, Narges; Weikert, Cornelia; Müller-Graf, Christine; Engel, Christoph; Wirkner, Kerstin; Baber, Ronny; Laux, Peter; Luch, Andreas; Giulbudagian, Michael (PloS one, 2025)
Tattoos and permanent make-up (PMU) gain increasing popularity among the general population. There are indications that pigments or their fragments may translocate within the body, however knowledge about possible systemic adverse effects related to tattoos is very limited. We investigated the prevalence of systemic chronic health effects including cardiovascular diseases, cancer and liver toxicity and their relationship with the presence and characteristics of tattoos and PMU as part of the LIFE-Adult-study, a population-based cohort study. The control group without tattoos was from the same cohort and adjusted for confounders based on age, sex, smoking-status, body mass index, alcohol consumption and socioeconomic status. Of 4,248 participants, 7.4% (n = 320) had either a tattoo (4.7%; n = 199) or a permanent make-up (3.1%; n = 135), or both (n = 14). Thereof 5% (16/320) reported medical complications, i.e. pain, itch, swelling, infections, or allergic reactions, in relation to their tattoos or PMUs. Regarding systemic chronic health effects, increased risk ratios among the tattooed population were found for cardiovascular diseases and liver toxicity. For non-melanoma skin cancer, results from the tattoo questionnaire gave no indication for any tumour development at the site of the tattoo. Our results demonstrate an increased risk for cardiovascular and liver effects in participants bearing a tattoo. Strong differences in the observed effects between men and women point on the presence of a sex-specific bias. Even if no statistically robust conclusion can be drawn due to the small sample size, the results suggest that cardiovascular outcomes and liver toxicity in tattooed individuals should be investigated further using prospective designs in larger cohorts.